Analisis Pengaruh Budaya Kerja Islam dan Motivasi Kerja terhadap Kinerja Pegawai Kementerian Agama Sidoarjo - Andika Radyasasmita,; Suryaningsih, Sri Abidah (Jurnal Ekonomika dan Bisnis Islam, 2022)
This research was aim to determine the effect of islamic work culture and work motivation on employee performance at the office of Ministry of Religion Sidoarjo. The approach that do to this research using quantitative approach. Variable that used on this research is islamic work culture (X1) and work motivation (X2) as independent variable and employee performance as dependent variable (Y). Population that used on this research is the employee at Ministry of Religion office. Data that used is primer data type, with the accumulation technic data by offline questionaire which containe some statement that support the succesment of the research. The answer from respondent be measured by likert scale. This questionnaire was tested using validity and reliability tests. This research uses descriptive analysis method and simple linear regression analysis. The result of this research indicated that Islamic work culture and work motivation had a parcial positive and significant effect on the employee performance of the Sidoarjo Ministry of Religion office. Significance value < 0,05 describe Islamic work culture and work motivation had a simultaneous and significant on the employee performance. The value of the coefficient of determintation (R2) is 0.572 its means that the variabel of Islamic work culture and work motivation have 57% effect on the work performance variable of the Sidoarjo Ministry of Religion office employees, the rest is influenced by other variables that not examined in this research.